2009
DOI: 10.1111/j.1369-7625.2009.00561.x
|View full text |Cite
|
Sign up to set email alerts
|

User involvement in the construction of a mental health charter: an exercise in communicative rationality?

Abstract: Background This paper uses Ju¨rgen HabermasÕs Theory of Communicative Action as a lens through which to examine the development of a local mental health charter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 18 publications
(10 reference statements)
0
27
0
Order By: Relevance
“…( , p. 55) Furthermore, a non‐judgemental approach, acknowledging people's views and experiences and considering the reasons behind behaviour rather than making a judgement were also identified. Research by Hodge highlighted the lack of ‘professional listening’ services and psychological therapies. Both Rush and Kemp found that service user involvement in the classroom provided student mental health nurses with the opportunity to see service users in recovery, rather than only in the in the acute stages of their illness, as would often be the case in placements in practice settings.…”
Section: Findings and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…( , p. 55) Furthermore, a non‐judgemental approach, acknowledging people's views and experiences and considering the reasons behind behaviour rather than making a judgement were also identified. Research by Hodge highlighted the lack of ‘professional listening’ services and psychological therapies. Both Rush and Kemp found that service user involvement in the classroom provided student mental health nurses with the opportunity to see service users in recovery, rather than only in the in the acute stages of their illness, as would often be the case in placements in practice settings.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…A person-centred approach Valued characteristics of person-centred care found in the sample of literature were empathy and respectful listening, 7,23-30 treating service users with dignity and/or respect, 25,[31][32][33][34] being respected as an individual 7,25,31,33,35 and trust. 36 Building a therapeutic relationship was considered important by Greaves 24 and Borg et al 5 who suggested that this required interest in and awareness of the service user's daily life and difficulties.…”
Section: Key Attributes Of the Concept Of Service User Involvementmentioning
confidence: 99%
“…Somewhat paradoxically, critically minded service users have capitalized on a distinctly consumerist turn in social policy attendant on neoliberal assertions of the primacy of individualism and personal choice. A consumerist framing perhaps explains both the general lack of transformative impact of what passes for standard user involvement initiatives (see Suzanne Hodge , ) and the ever present hazard of co‐option. Cooke & Kothari () view such participation as akin to a new form of tyranny, too readily incorporated into established systems of governance and control.…”
Section: Listening For a Squawk Of Resistancementioning
confidence: 99%
“…Habermas's 24,25 communicative action theory was drawn on to make sense of this, and has been similarly deployed regarding involvement initiatives in mainstream mental health settings. [26][27][28] For Habermas, change is driven by communication and forms of deliberative, participatory democracy. Ideally, participants should enter into these interactions with equal power, respect and open minds.…”
Section: Involvement Practices In Secure Settingsmentioning
confidence: 99%